PREVENTION OF SURGICAL SITE INFECTIONS: A COMPREHENSIVE REVIEW OF GUIDELINES AND SCIENTIFIC EVIDENCE (2017–2025) - Jakub Tomasz Latos,; Katarzyna Anna Kowalska,; Franciszek Szweda,; Tomasz Poczwardowski,; Adrianna Kaczmarek,; Marcin Chwalczuk,; Olivia Grygorcewicz,; Marta Koneczna,; Karolina Alicja Krystyniak,; Kinga Augustyniak,; Klaudia Leszto,; Natalia Smuniewska, (International Journal of Innovative Technologies in Social Science, 2026)
Surgical site infections (SSIs) remain one of the most significant challenges in modern medicine, representing a major cause of patient morbidity, prolonged hospitalization, and increased healthcare costs in medical institutions. This issue deserves particular attention due to the possibility of preventing adverse outcomes through the implementation of standardized, evidence-based preventive measures approved by international health authorities. This narrative review examines recommendations aimed at reducing the incidence of SSIs based on publications indexed in major scientific databases, along with guidelines issued by the World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), European Centre for Disease Prevention and Control (ECDC), and the National Institute for Health and Care Excellence (NICE). The article focuses on perioperative recommendations, categorized as preoperative, intraoperative, and postoperative, while considering both the strength of evidence and areas of consistency or divergence among these guidelines. Researchers worldwide generally agree on the most essential preventive strategies, including proper timing of antimicrobial prophylaxis, the use of chlorhexidine-based antiseptics, maintenance of normothermia and glycemic control, and avoidance of unnecessary hair removal. However, differences persist in certain preventive components, such as the use of advanced wound dressings, intraoperative oxygen supplementation, and mechanical barriers, highlighting the need for further discussion and harmonization of global standards. The review emphasizes the importance of implementing these guidelines in clinical practice and identifies unresolved issues requiring additional research. Strengthening education among healthcare professionals and ensuring adherence to correct perioperative practices under expert supervision will undoubtedly contribute to improved surgical outcomes and reduced infection-related complications worldwide.